Work Family Enrichment and Life Satisfaction among Women in IT Sector - Ragles Devi, K.; Sakthivelrani, S. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
The expectation and exact discoveries with respect to work–family enhancement and fulfillment has been inconsistent in previous research. The existing study inquire about tries to clear up this irregularity by looking at both bearings of work–family improvement with both employment and family fulfillment to figure out whether their belongings are comparable/differing. Data was gathered using self structured questionnaire and a sample of 653 respondents were chosen among women professionals working in IT sector. Regression, correlation and structural equation modeling analysis were used to check how Work family enrichment has direct effect on life satisfaction. However, the impact on employment fulfillment is solidly based on enhancement from descendents to work rather than job to family enrichment. Keywords: Work to family enrichment, Family to work enrichment, Life Satisfaction, Family satisfaction, Job satisfaction and Women employees.